Scaffold-mediated sequential drug/gene delivery to promote nerve regeneration and remyelination following traumatic nerve injuries - Ong, William (2020)
Neural tissue regeneration following traumatic injuries is often subpar. As a result, the field of neural tissue engineering has evolved to find therapeutic interventions and has seen promising outcomes. However, robust nerve and myelin regeneration remain elusive. One possible reason may be the fact that tissue regeneration often follows a complex sequence of events in a temporally-controlled manner. Although several other fields of tissue engineering have begun to recognise the importance of delivering two or more biomolecules sequentially for more complete tissue regeneration, such serial delivery of biomolecules in neural tissue engineering remains limited. This review aims to highlight the need for sequential delivery to enhance nerve regeneration and remyelination after traumatic injuries in the central nervous system, using spinal cord injuries as an example. In addition, possible methods to attain temporally-controlled drug/gene delivery are also discussed for effective neural tissue regeneration.